A Mini Review on the Biodegradation of Petroleum Hydrocarbon Pollutants by the Genus Rhodococcus - Abd Ghani, Shafinaz; Habib, Syahir; Yasid, Nur Adeela; Ahmad, Siti Aqlima; Shukor, Mohd Yunus (Journal of Environmental Microbiology and Toxicology, 2018)
The genus Rhodococcus is a very diverse group of Eubacteria that are commonly found in many environmental niches such as soils and seawaters likewise. Owed to their remarkable range of varied catabolic gene and robust cellular physiology, this genus is competent to degrade a great number of organic compounds including some of the most difficult compounds such as petroleum hydrocarbons. This review discusses two interrelated topics, which are the petroleum hydrocarbons pollution in the environment and the utilization of the Rhodococcus genus in microbial remediation of petroleum hydrocarbons and its derivatives. The first part focuses on the application of hydrocarbon components in standard routine, sources of pollution and the toxicity of these compounds. On the second fraction of this assessment, the biochemistry, physiology and genetic versatility of the genus Rhodococcus will be reviewed with emphasizing their significance in environmental biotechnology and bioremediation of petroleum hydrocarbons.